Pengaruh Kesiapan UMKM Dalam Penerapan SAK EMKM (Studi kasus UMKM Tenun Ikat di Kabupaten Sikka) - Matheus Yandris; Wilhelmina Mitan; Paulus Libu Lamawitak (Universitas 45 Surabaya, 2023)
The purpose of this study was to determine the effect of educational background, business size, business age and SAK EMKM socialization on the readiness of UMKM Ikat Weaving in Sikka Regency in compiling financial reports based on SAK EMKM. This study uses a quantitative approach with primary data obtained from questionnaires distributed. The population in this study are SMEs engaged in the Ikat Weaving business in the Sikka district. The data analysis method uses regression analysis with the help of the SPSS Statistics version 22 program. The results of this study state that the variables of educational background, business size, business age, and socialization of SAK EMKM partially and simultaneously have a significant effect on the readiness of MSMEs in implementing financial reports based on SAK EMKM .